2021
DOI: 10.1016/j.biopsych.2020.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of Cortical Degeneration Over a Decade in Huntington’s Disease

Abstract: Background Characterizing changing brain structure in neurodegeneration is fundamental to understanding long-term effects of pathology and ultimately providing therapeutic targets. It is well established that Huntington’s disease (HD) gene carriers undergo progressive brain changes during the course of disease, yet the long-term trajectory of cortical atrophy is not well defined. Given that genetic therapies currently tested in HD are primarily expected to target the cortex, understanding atrophy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
(78 reference statements)
2
38
1
Order By: Relevance
“…Overall, the evidence from observational studies relating change in clinical outcomes to change in vMRI metrics appears sparser than the cross-sectional relationships described earlier, with the strongest longitudinal relationships relating rates of brain volume loss to changes in cognitive and composite measures rather than purely motor measures ( 2 , 19 , 20 , 64 , 66 ) ( Figure 6 ). For example, these studies have revealed relatively weak longitudinal associations between change in vMRI and change in UHDRS-TMS over a typical clinical trial time frame (1–2 years), despite the presence of a significant cross-sectional relationship between them.…”
Section: Relationships Between Longitudinal Change In Both Regional Brain Volumes and Clinical Outcome Measuresmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall, the evidence from observational studies relating change in clinical outcomes to change in vMRI metrics appears sparser than the cross-sectional relationships described earlier, with the strongest longitudinal relationships relating rates of brain volume loss to changes in cognitive and composite measures rather than purely motor measures ( 2 , 19 , 20 , 64 , 66 ) ( Figure 6 ). For example, these studies have revealed relatively weak longitudinal associations between change in vMRI and change in UHDRS-TMS over a typical clinical trial time frame (1–2 years), despite the presence of a significant cross-sectional relationship between them.…”
Section: Relationships Between Longitudinal Change In Both Regional Brain Volumes and Clinical Outcome Measuresmentioning
confidence: 92%
“…Voxel-wise analyses have also identified increasing losses of gray matter volume in the occipital, parietal, frontal and insular cortices as the disease advances ( 2 , 63 ). A recent dynamic modeling approach that used 6 years of TRACK-HD and Track-On HD data revealed a temporal sequence of regional changes around the time of clinical motor diagnosis that involves not only the caudate and putamen but also cortical regions, including sensorimotor areas ( 64 ).…”
Section: Mri Brain Volume Measurements Have Robust Longitudinal Change Characteristicsmentioning
confidence: 99%
“…The mutant huntingtin protein (mHTT) that results from CAG repeat expansion affects many cellular functions, leading to cell death, and establishing which of these effects are primary or secondary pathogenic processes is difficult. Striatal medium spiny neurons are most vulnerable to the presence of mHTT, although substantial neuronal dysfunction and death also occurs in the cerebral cortex [14][15][16][17][18] .…”
Section: [H1] Introductionmentioning
confidence: 99%
“…Usually, cognitive impairments exhibited in HD patients are associated to caudate nucleus decrease due to the spiny neurons atrophy [ 31 ]. This decrease seems to affect particularly the caudate nucleus during the clinical debut, specially compromising the prefrontal cortico-striatal loop [ 2 , 32 , 33 ]. However, our study found that putamen deterioration in HD patients also contributes to the accuracy decrease to solve planning problems.…”
Section: Discussionmentioning
confidence: 99%